Urgensi Qashah Al Qur’an Sebagai Metode Pembelajaran Yang Efektif Di Program Studi PBA UINSU Stambuk 2020 - Rifqi Ivan Hadi Tama; Muhammad Alfiansyah; Dedi Masri; Maryam Hafidzah; Albaiyah (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
This research was conducted to determine the effectiveness of the Qur'an qashash method used in educational institutions, especially at the State Islamic University of North Sumatra in the Arabic Language Education study program. This study uses several basic methods in writing scientific papers. By collecting several reading references or using the literature study method and at the same time distributing questionnaires in the form of question variables through the Google form media. The research shows the respondents' understanding of the Al-Qur'an qashash method which is an illustration of the effectiveness of Al-Qur'an qashash-based learning methods.